High-performance web services for querying gene and variant annotation. Issue 1 (December 2016) - Xin, Jiwen; Mark, Adam; Afrasiabi, Cyrus; Tsueng, Ginger; Juchler, Moritz; Gopal, Nikhil; Stupp, Gregory; Putman, Timothy; Ainscough, Benjamin; Griffith, Obi; Torkamani, Ali; Whetzel, Patricia; et al.
Abstract Efficient tools for data management and integration are essential for many aspects of high-throughput biology. In particular, annotations of genes and human genetic variants are commonly used but highly fragmented across many resources. Here, we describe MyGene.info and MyVariant.info, high-performance web services for querying gene and variant annotation information. These web services are currently accessed more than three million times per month. They also demonstrate a generalizable cloud-based model for organizing and querying biological annotation information. MyGene.info and MyVariant.info are provided as high-performance web services, accessible athttp://mygene.info andhttp://myvariant.info . Both are offered free of charge to the research community.